2012
DOI: 10.1051/0004-6361/201117704
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in M 67: From the main sequence to the red giant branch

Abstract: Context.Lithium abundances in open clusters are a very effective probe of mixing processes, and their study can help us to understand the large depletion of lithium that occurs in the Sun. Owing to its age and metallicity, the open cluster M 67 is especially interesting on this respect. Many studies of lithium abundances in M 67 have been performed, but a homogeneous global analysis of lithium in stars from subsolar masses and extending to the most massive members, has yet to be accomplished for a large sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 107 publications
(167 reference statements)
3
66
2
3
Order By: Relevance
“…Compared to the values reported by Takeda et al (2013) and Pace et al (2012), WASP-18 has a slightly higher Li abundance. Lithium depletion is due to the convective mixing during the main sequence life of a star, so Li abundance is a rough indicator of youth in solar type stars with deep convective zone.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Compared to the values reported by Takeda et al (2013) and Pace et al (2012), WASP-18 has a slightly higher Li abundance. Lithium depletion is due to the convective mixing during the main sequence life of a star, so Li abundance is a rough indicator of youth in solar type stars with deep convective zone.…”
Section: Discussioncontrasting
confidence: 65%
“…However, the scenario becomes more puzzling when considering that WASP-18 shows Li absorption at 6708 Å, with a value typical of, or even stronger than values found in F-late stars of Hyades (Takeda et al 2013) and M 67 (Pace et al 2012). Figure 3 shows a portion of the spectrum of WASP-18 around the Li doublet lines at 6708 Å, and Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This spread has been noticed in previous works, such as Pace et al (2012), where they show how Li abundances do not depend on mass for solar type stars (one solar mass or lower) in M67, and they suggest that an extra variable, in addition to mass, age, and metallicity, is responsible for the scatter in Li abundances, since those stars are very similar. A similar spread in Li is observed for field stars around one solar mass and −0.2 < [Fe/H] < 0 in Lambert & Reddy (2004).…”
Section: And Stellar Masssupporting
confidence: 74%
“…Chaboyer et al 1995;Charbonnel & Talon 2005), that account for the destruction of Li observed in solar-type stars in open clusters and in the field (e.g. Pace et al 2012). As seen in Fig.…”
Section: Discussionmentioning
confidence: 96%